PENGARUH INHALASI SEDERHANA MENGGUNAKAN AROMATERAPI DAUN MINT (MENTHA PIPERITA) TERHADAP PENURUNAN SESAK NAFAS PADA PASIEN TUBERCOLOSIS PARU DI PUSKESMAS - Vitrilina Hutabarat; Stefani Anastasia Sitepu; Megawati Sinambela (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
Background: Simple inhalation is a method of treatment by giving the drug in the form of vapor directly to the respiratory tract to the lungs. Shortness of breath in pulmonary tuberculosis will be found in advanced disease, where the filtration is half the lung. This symptom is found in the lung parenchymal damage is extensive. Therefore found a way to reduce shortness of breath, one of them with simple inhalation using aromatherapy mint leaves (Mentha Piperita). This study aims to determine the effect of simple inhalation using aromatherapy mint leaves (Mentha Piperita) on decreasing shortness of breath in pulmonary tuberculosis patients. Method: This study uses one group pre-test and post-test design. In this study, the data were analyzed by the T-independent test. Result: Based on the T-independent test results, the treatment group shows that there is a simple inhalation using aromatherapy mint leaves (Mentha Piperita) to decrease breathlessness in pulmonary tuberculosis patients. Looking at the results of this study, simple inhalation using aromatherapy mint leaves (Mentha Piperita) can be used as a non-pharmacological therapy to reduce clinical symptoms of tuberculosis, namely shortness of breath.